The Effect of Various Surface Functionalizations of Core–Shell Nanoactuators on Magnetoelectrically Driven Cell Growth; ACS Applied Materials & Interfaces; Vol. 17, iss. 14 - Chernozem P. V. Polina Viktorovna; Romashchenko A. V. Aleksandr Viktorovich; Solovieva O. I. Olga; Ibraeva A. Zh. Azhar Zhangeldinovna; Nosov G. Georgy; Koptsev D. A. Danila Andreevich; Lisitsyn S. Sergey; Surmeneva M. A. Maria Alexandrovna; Vagner D. Dmitry; Gerasimov E. Yu. Evgeny; Kazantsev S. O. Sergey Olegovich; Lozhkomoev A. S. Aleksandr Sergeevich; et al. (2025, 2025)
Title screen